Respiratory long COVID in aged hamsters features impaired lung function post-exercise with bronchiolization and fibrosis - Laura Heydemann; Małgorzata Ciurkiewicz; Theresa Störk; Isabel Zdora; Kirsten Hülskötter; Katharina Manuela Gregor; Lukas Mathias Michaely; Wencke Reineking; Tom Schreiner; Georg Beythien; Asisa Volz; Tamara Tuchel; et al. (Nature Communications)
Abstract Long-term consequences of SARS-CoV-2 infection affect millions of people and strain public health systems. The underlying pathomechanisms remain unclear, necessitating further research in appropriate animal models. This study aimed to characterize the trajectory of lung regeneration over 112 days in the male hamster model by combining morphological, transcriptomic and functional readouts. We demonstrate that in the acute phase, SARS-CoV-2 Delta-infected, male, aged hamsters show a severe impairment of lung function at rest. In the chronic phase, similar impairments persisted up to 7 weeks post-infection but were only evident after exercise on a rodent treadmill. The male hamster model recapitulates chronic pulmonary fibrotic changes observed in many patients with respiratory long COVID, but lacks extra-pulmonary long-term lesions. We show that sub-pleural and interstitial pulmonary fibrosis as well as alveolar bronchiolization persist until 112 dpi. Interestingly, CK8+ alveolar differentiation intermediate (ADI) cells are becoming less prominent in the alveolar proliferation areas from 28 dpi on. Instead, CK14+ airway basal cells and SCGB1A1+ club cells, expressing cell proliferation markers, mainly populate alveolar bronchiolization areas at later time-points. We postulate that pulmonary fibrosis and SCGB1A1+ club cell-rich areas of alveolar bronchiolization represent potential risk factors for other diseases in long-COVID survivors.